Risk Assessment of Heavy Metals in Chromolaena odorata Collected Around Gemstone Mining Site in Ijero-Ekiti - Efe Sylvanus Abiya; Foluso Akinbode Ologundudu; Ekpo wisdom (Biology, Medicine, & Natural Product Chemistry, 2021)
In Nigeria, like many developing nations, the resultant effect of land degradation: aggravated soil erosion, flood disasters, salinization or alkalisation, and the desertification have been a major public health concern for the past decades, however this study highlighted some of the factors that leads to the menace of soil fertility. The study was conducted at a gemstone mining site in Ijero Ekiti, Ekiti State, Nigeria. The soil samples were collected at a depth of 0-15 cm top soil and 0-30 cm subsoil. A line transect of 20 cm was drawn and soil sample was collected, all samples were kept in a clean container and labeled accordingly before been transported to the laboratory for analysis. The plant samples were thoroughly washed with distilled water to remove dust and other particles, air dried in a dust free wire meshed cage. All data obtained from this research were subjected to one-way analysis of variance (ANOVA). The result obtained in this study indicated that the levels of heavy metal concentration tested were still within the permissible limit in the root and shoot of Chromolaena odorata between the mine and control site. The implication of this is that Chromolaena odorata is safe for human and animal consumption. The said plant can readily undergo photosynthetic activity to aid growth by exploiting the presence of these metals either as a macro-nutrient or micro-nutrient as seen from the Translocation Factor and Metal Transfer Factor. The study concludes that soil at Ijero-Ekiti mine site were slightly acidic soil pH, reduced organic carbon, total nitrogen, available phosphorus, exchangeable cations and averagely elevated heavy metal contents.